Estimation of Modal Properties of Low-Rise Buildings Using Ambient Excitation Measurements - K. K. Wijesundara; C. Negulescu; E. Foerster (Shock and Vibration)
Continuous wavelet transform (CWT) has recently emerged as a promising tool for identification of modal properties through ambient excitation measurements of structures. However, it is difficult to obtain an accurate estimation of damping ratio directly from time-frequency decomposition of ambient vibration measurements using CWT. The main objective of this study is to introduce a new method called two-step procedure in the estimation of damping ratios using ambient vibration measurements. The two-step procedure involves the development of random decrement (RD) signature from the ambient vibration measurements, which is equivalent to the damped free vibration response of a structure under a given initial displacement and subsequently decomposition of time domain RD signature into time-frequency domain using CWT. The secondary objective of the study is to show that CWT is capable of identifying the natural periods and mode shapes of low-rise buildings using ambient vibration measurements. Furthermore, the two-step procedure is validated with two practical applications in a five-storey reinforced concrete structure with masonry infill walls and a three-storey masonry structure. Finally, a conclusion can be drawn that the two-step procedure yields a reasonably good estimation of damping ratio.